The Use of Massage With Olive Oil To Reduce Nocturnal Enuresis In Preschool Children - LESTARININGSIH, SRI; TRIWIJAYANTI, YOGA (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to determine the use of massage with olive oil to reduce nocturnal enuresis in preschool children. The research method used the pretest and post-test group design of the pre-experimental research, involved a total of 30 respondents, with 30 respondents for each treatment group. Data collection uses a checklist. This analysis uses a statistical T-Test Dependent (Paired T-Test). the final results of the study show the frequency distribution of children who experienced mild enuresis were 12 respondents (40%), children who experienced moderate enuresis were 2 respondents (6.7%), and children who experienced severe enuresis were 16 respondents (53.3%). after being given a massage using olive oil, there was a decrease in the number of children experiencing nocturnal enuresis with the results of 19 respondents (63.3%) of children without enuresis, children with mild enuresis being 9 respondents (30%), children with moderate enuresis were only 2 respondents (6.7%), and no children with severe enuresis were found. Statistical test results obtained P-value 0,000, which means there is an influence of the use of massage with olive oil with a decrease in enuresis in preschool children.